Confinement practices among postnatal mothers in Hospital Universiti Sains Malaysia - Hong, Angela Lee Leh (Universiti Sains Malaysia, 2023)
Recognition of confinement practices and their diet among postnatal mothers including the duration of confinement period are some aspects that need to be aware of to make sure they have adequate rest and nutrition. A cross-sectional study was designed to determine the duration of confinement practices, the practice that has been practiced during the confinement period, and identify the frequency of foods and dietary intake during the confinement period among the postnatal mothers at Hospital USM. A total of 357 respondents were recruited through the convenience sampling method. Data were collected by using self-administered questionnaires. Data collected were statistically analyzed using the Statistical Package Social Sciences (SPSS) software version of 26. Content validation of the instrument was done and the reliability was obtained through a pilot study with Cronbach’s alpha of 0.825. This study shows that more than half of the respondents had 30-40 days of confinement period (52.9%). The findings also demonstrated that more than half of the respondents had a massage (85.7%), consumed traditional herbs/ jamu (50.7%), and had restrictions to go out (58.8%) during the confinement period. Furthermore, more than half of the respondents had more plain water (71.4%), fish (71.1%), ginger (51.8%), and leafy vegetables (51.3%) during their confinement period. The significant predicting factors for the duration of the confinement period are parity, educational level, race, occupational status, and monthly salary which p<0.05.